Halide perovskite materials as chemical playground. Issue 9 (31st August 2022) - Hutter, Eline M.
Abstract: Due to their excellent optoelectronic performance, and relatively easy processibility, halide perovskite semiconductors are used in highly efficient solar cells, LEDs, X‐ray detectors, and more recently in photo(electro)chemistry. Eline M. Hutter aims to obtain stable, non‐toxic perovskites for photoconversion applications.